Burkitt's Lymphoma Mimicking a Subacute Subdural Hematoma: a Case Report - Souza Filho, Lucidio Duarte de; Belo, João Tiago Alves; Cunha, Pedro Henrique Martins; Faleiro, Rodrigo Moreira (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2016)
Burkitt's lymphoma (BL) is a highly aggressive B cell non-Hodgkin lymphoma. Although dural metastases are relatively frequent in malignancies, they are rarely associated with subdural hematoma (SDH). We present a case of subdural effusion secondary to dural metastases from Burkitt's lymphoma.
Keywords: burkitt's lymphoma; subdural hematoma